Hematological inflammation biomarkers in patients with pseudoexfoliation syndrome and pseudoexfoliation glaucoma - Alper Can Yilmaz; Hayati Yilmaz (International Journal of Ophthalmology)
AIM: To evaluate complete blood count and biochemical parameters in patients with pseudoexfoliation syndrome (PEXS) and pseudoexfoliation glaucoma (PEXG) and compare the results with healthy controls. METHODS: Forty-four patients with PEXS, 61 patients with PEXG, and 55 healthy subjects were enrolled in this retrospective study. All systemic and especially pseudoexfoliation-related ophthalmic examination findings of the participants were evaluated. Complete blood count, glucose, creatinine, and serum lipid values ??were obtained. In line with these data, monocyte-to-lymphocyte ratio, neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio, monocyte-to-high density lipoprotein (HDL) ratio (MHR), and mean platelet volume-to-platelet count ratio were obtained and comparison were made among groups. RESULTS: Diabetes mellitus and hypertension were significantly more common in the PEXS and PEXG groups than in the control group (P=0.021, P=0.016, respectively). In the analysis of complete blood count parameters, NLR and MHR values ??were statistically significantly higher in PEXS and PEXG compared to the control group (P=0.037, P=0.025, respectively). In addition, glucose, low-density lipoprotein, and triglyceride values ??were significantly higher in the PEXS and PEXG groups compared to the control group (P<0.001, P=0.035, P<0.001, respectively), and HDL value was significantly lower (P=0.031). CONCLUSION: The hematological inflammation biomarkers we evaluated in our study provide evidence that systemic inflammation and oxidative stress processes play an important role in the pathogenesis of PEXS and PEXG.